Шекспир, Шопен, Рембрандт и другие: Концепция гения в христианской парадигме Бориса Пастернака - Malcewa, Oksana (Acta Polono-Ruthenica, 2018)
In the present article historical and cultural allusions in the cycle A Midsummer Night’s Dream by B. Pasternak (from his book Themes and Variations, 1916-1922) are analyzed. The special attention is paid on artistic interpretation of the images of Shakespeare, Chopin, Rembrandt and others. Peculiarities of the Russian poet’s conception of genius as a phenomenon of grace of God are investigated.